Big Five Personality Traits and Employee Performance: Evidence from Mediation and Moderation Analysis - David Desaili; Widiya Dewi Anjaningrum; Vivien Amor Viloria (Department of Management, Faculty of Economics, Universitas Negeri Malang, 2023)
In response to heightened university competition, Institut Teknologi dan Bisnis Asia Malang has witnessed a decline in students' enrollment. To navigate this challenge, the institution aims to establish a competitive edge by adopting the resource-based view theory. This strategic approach emphasizes the unique qualities of the institution's resources, with human capital emerging as the most pivotal. This study involves 120 respondents, exploring the influence of Big Five personality traits, organizational commitment, and attitude toward digital work on employee performance. Using the partial least square structural equation modelling (PLS-SEM) method, the findings indicate that the Big Five personality traits insignificantly impact employee performance. The Big Five personality traits significantly impact organizational commitment, and organizational commitment significantly impacts employee performance, in which the organizational commitment serves as a complete mediation. In addition, attitudes towards digital work as quasi-moderating can strengthen the influence of the Big Five personality traits on employee performance. Further research is recommended to analyze the relationship between the dimensions of each variable in more depth.   Keywords: Big five personality traits, Organizational commitment, Attitude toward digital work, Employee performance